Staffing and patient-related factors affecting inpatient falls in a psychiatric hospital: a 5-year retrospective matched case–control study - Acharaporn Seeherunwong (2022)
Background: The frequency and severity of falls of psychiatric inpatients in Thailand have not been previously reported. Also, the risk factors of falls have been numerous and complicated. This study aimed to investigate the staffing factors and patient-related factors that increase the likelihood of falls among psychiatric inpatients. Methods: A five-year retrospective matched case–control study was conducted that selected cases of inpatients who fell and which were reported to the hospital risk management system. Subjects were compared to two control patients from the same hospital (1:2) by age (± 5 years), sex, and admission the same year. The total sample consisted of 240 patients. Univariate and multivariate conditional logistic regression was used to analyze the data. Results: Of the eighty falls, 86.3% resulted in temporary harm and required intervention. The multivariate model showed that three patient-related factors were associated with increased inpatient falls: (1) having an acute psychotic condition (adjusted odds ratio (AOR) = 4.34; 95% CI 1.45, 13.05; p < 0.05), (2) polypharmacy with more than four types of medicines (AOR = 3.06; 95% CI 1.59, 5.88; p < 0.05), and (3) taking atypical psychiatric drugs (AOR = 2.74; 95% CI 1.35, 5.58; p < 0.05). Staffing for 26–50 patients in the wards was more protective for falls than with 25 or fewer patients (AOR =.17; 95% CI 0.04, 0.72; p < 0.05). Conclusions: The risk factors found may help assess fall risk and manage the number of patients in psychiatric units. Drug dosage and drug interaction of antipsychotic drugs and cardiovascular agents with other medications and drug administration timing before falls are recommended for further investigation. Also, staff ratio per patient and the proportion of staff mix in psychiatric units need further study to establish adequate levels of surveillance to prevent inpatient falls.